Extraction and Application of Natural Colourant from the Bark of Berlinia Grandiflora on Cotton and Polyamide 6 Fabrics - Asiagwu, A.K.; Otutu , J.O.; Onyesom, I.E.; Ebigwai, J.K. (Iraqi Journal of Science, 2021)
The aim of this study is to extract and utilise the bark of Berlinia grandiflora as a natural dye source for the colouration of cotton and polyamide 6 fabrics. The solvents used for this study were water, methanol, acetone, and methanol/potassium hydroxide. The best of all the solvents used was water. In the extraction process, the various solvents were extracted with Soxhlet extractor. The optimum colourant extraction was observed at 40 °C for 2 h. The extracted compound was isolated and characterized by UV spectrophotometry; proton and carbon-13 nuclear magnetic resonance, mass spectrometry, and Fourier transform infrared spectroscopy. Mordanting and subsequent dyeing of cotton and polyamide 6 fabrics with the extracted colourant were performed to investigate the dye’s efficiency. Two metal salts, namely copper sulphate and stannous chloride, were used as mordants. Furthermore, the washing, rubbing, and light fastness properties of dyed samples were tested. The results of the fastness tests showed that the natural dye gave light fastness value (3= fair) without the use of mordants, whereas the values were 5 on cotton and 4 on nylon 6 with the use of mordants. The results of fastness of rubbing and washing were excellent for both cotton and nylon. The outcome of the study presents a potentially useful natural colourant for the colouration of natural and synthetic fibers.